If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 = -6x + x + -2 Reorder the terms: 18 = -2 + -6x + x Combine like terms: -6x + x = -5x 18 = -2 + -5x Solving 18 = -2 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. 18 + 5x = -2 + -5x + 5x Combine like terms: -5x + 5x = 0 18 + 5x = -2 + 0 18 + 5x = -2 Add '-18' to each side of the equation. 18 + -18 + 5x = -2 + -18 Combine like terms: 18 + -18 = 0 0 + 5x = -2 + -18 5x = -2 + -18 Combine like terms: -2 + -18 = -20 5x = -20 Divide each side by '5'. x = -4 Simplifying x = -4
| (x-5)/10+(1+2x)/5=(3-x)/4 | | 40*2=110/1,5 | | 2m+4m-3=9 | | -x/12=-1 | | x+6=34*1.5 | | 5x^2+25x+20= | | -68=x+7x+4 | | 3x-2=34*2 | | 11(x-2)=6x+13 | | 3(x+1)+37=-2x | | x+x+6+3x=86 | | 9x+7=5x+11 | | 3x-2=13x-61 | | x-76/7=4/5 | | n/6+6=8 | | 81y^2=25 | | -9(-8)-8= | | 3(X-5)+4=(x+4)-2 | | (8x+10)2=12x+40 | | 6x+7=5x+3 | | (-9-8)-8= | | 2/247=x | | p+c=12 | | 9b^2-14b-8=0 | | 7(x-3)+5=3(X+3)-4 | | x-4/9=5/6 | | -9-7x-6x=134 | | 11x+5=4x+26 | | 3(4x+7)=45 | | -4+10i=0 | | 40+4y-8=15y-10-5y | | 10(x-4)=4x+-16 |